Analisis pelaksanaan kebijakan program keluarga berencana (KB): studi kasus di Kabupaten Malinau - Priscilla Bawing; Retna Siwi Padmawati; Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2017)
Implementation of district level "four children better" family planning policy in MalinauPurposeThis study aimed to analyze the implementation of family planning program policy in Malinau.MethodsA case study was conducted through in-depth interviews with 18 participants.ResultsThe policy of the government in Malinau is ‘four children are better’. Differences in perceptions between stakeholders, providers, and users about family planning affecting social, economic, cultural, beliefs have an impact on contraceptive use in Malinau. The use of contraception is not prohibited for people with medical indications for using contraception, but people should access the contraception independently in the private sector.ConclusionThe policy of the Malinau government to stop the supply of contraceptives to government health facilities since 2012 is an effort by local governments to increase the number of inland and border populations. The unavailability of contraceptives in government health facilities and the limitations of family planning information, communication and education lead to differences in perceptions between stakeholders, service providers, and users. Therefore, the researcher recommends that the relevant regional apparatus unit does advocacy to legislative and executive boards in Malinau. The local government shall ensure the availability and quality of family planning services for the community on the basis of reproductive health rights.